1992
DOI: 10.1182/blood.v80.4.1058.1058
|View full text |Cite
|
Sign up to set email alerts
|

Blood platelets stimulate the expression of chondroitin sulfate proteoglycan in human monocytes

Abstract: Mononuclear phagocytes synthesize chondroitin sulfate proteoglycan (CSPG), which is constitutively secreted. Because mononuclear phagocytes are known to interact with blood platelets, the effect of platelets on the release of CSPG in cultured human monocytes was investigated. After 6 days in vitro, the monocytes were supplied with fresh medium with different additions and subsequently exposed to [35S]sulfate for 24 hours before the medium fractions were harvested and analyzed for content of [35S]CSPG. Indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
5
28
0
Order By: Relevance
“…We observed, in accordance with other studies, that the retina of the dystrophic RCS rat shows heavy accumulation of the N terminus of chondroitin sulfate proteoglycans [37], neurocan [38], and versican. Our results further demonstrated that microglia, which are known to produce CSPGs in vitro [39] and in vivo upon spinal cord injury [40,41], also express the N-terminal fraction of CSPGs, as well as neurocan and versican in the degenerating RCS rat retina. Significantly, costaining of retinal sections from transplanted RCS rat retinae for CSPGs and CD68 expression showed that microglia surrounding the grafted cells stained for CSPGs.…”
Section: Discussionsupporting
confidence: 73%
“…We observed, in accordance with other studies, that the retina of the dystrophic RCS rat shows heavy accumulation of the N terminus of chondroitin sulfate proteoglycans [37], neurocan [38], and versican. Our results further demonstrated that microglia, which are known to produce CSPGs in vitro [39] and in vivo upon spinal cord injury [40,41], also express the N-terminal fraction of CSPGs, as well as neurocan and versican in the degenerating RCS rat retina. Significantly, costaining of retinal sections from transplanted RCS rat retinae for CSPGs and CD68 expression showed that microglia surrounding the grafted cells stained for CSPGs.…”
Section: Discussionsupporting
confidence: 73%
“…Besides this effect, chlorate prevents scavenging of sulfate from cysteine (Krijgsheld et al, 1981) and reduces sulfate incorporation into PG, without affecting protein synthesis, phosphorylation, and cell morphology (Baeurle and Huttner, 1986;Rapraeger et al, 1991). On the other hand, p-xyloside derivatives at concentrations s 1 mM compete with endogenous xylosilated core proteins for GAG synthesis in a mode that is virtually confined to species containing chondroitid dennatan sulfate chains (Schwartz, 1977;Uhlin-Hansen and Kolset, 1988;Rapraeger, 1989;Kirby and Bentley, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This feature of hemopoietic cells is intriguing, because cells other than hemopoietic synthesize diverse types of proteoglycans (Poole, 1986). Intracellular serine-glycine-rich chondroitin sulfate proteoglycans (CS-PG) are generally stored as secretory granules by diverse types of hemopoietic cells (Hardin and Spicer, 1971;Uhlin-Hansen and Kolset, 1988;Krilis et al, 1992). The function of these components has not been fully elucidated.…”
mentioning
confidence: 99%
“…In addition, serglycin seems to be important in the regulation of the activity of the bound enzymes [9,10]. In contrast to the granular cells that store serglycin in the secretory granules, monocytes and lymphocytes secrete serglycin constitutively [11][12][13]. The secreted serglycin might serve as a carrier of other molecules, e.g., proteases and cytokines released from the cells.…”
Section: Introductionmentioning
confidence: 99%